Swimming training and pulmonary variables in women - Aydin, G.; Koca, I. (Journal of Human Sport & Exercise, 2014)
Most spirometry testing is done for patients with pulmonary problems not for general population samples (Enright and et. al., 2004) and not for the effect of training. Evaluation of the effect of exercise on diffusing capacity would be helpful to evaluate the ability of the pulmonary capillary bed to expand and increase its capacity to transfer gas during exercise (Wang, 2004). The purpose of this study was therefore to examine the effects of swimming technical skill training on pulmonary variables such as FVC (forced vital capacity), FEV1 (forced expiratory volume in one second), FEF25-75 (forced expiratory flow from 25% to 75%), MVV (maximal voluntary ventilation), ERV (expiratory reserve volume), VC (vital capacity), PEF (peak expiratory flow) in women. Nineteen women (swimming trained group= 11, control inactive group= 8) participated in this study. All the subjects with the exception of inactive control group participated in swimming technical skill training, three times a week for 12 weeks. Measurements were made before and after the swimming training for each subject with spirometer (Sensormedics Vmax 29 C). The swimming training program was designed on the basis of swimming skills including: breathing in water, sliding the body in water, free style and backstroke foot drills, arm-foot and breathing coordination drills with and without swimming board, free style and backstroke drills. It was found that swimming has a positive effect on FVC (forced vital capacity), FEV1 (forced expiratory volume in one second), MVV (maximal voluntary ventilation) (Akgün, 1986). According Khosravi, et. al. (2013) endurance training combined with resistance training has greater effect on VC, FVC, FEF rating at 25%-75%, and also on PEF except MVV. The following variables exhibited significant difference after the 3 months swimming technical skill training: MVV and PEF. Results indicated that swimming technical skill training during 12 weeks training had a significantly positive effect on pulmonary variables such as MVV, PEF but no significant changes were observed in FVC, FEV1, FEF %25-75, ERV, VC. Efficacy of respiratory and pulmonary functions has a direct relationship with general health. Exercise training improves endurance and strength of athletes` respiratory muscles; it also causes resistance reduction in respiratory canals, and increases lung elasticity and alveolar expansion as studies have supported the expansion of pulmonary volumes and capacities (Khosravi, et. al. 2013). As a conclusion of the present study suggest that swimming technical skill training can improve pulmonary function of women. According to a study (Armour, et. al, 1993) the increased lung volumes in swimming were not due to an increase in alveolar distensibility and may, therefore, have been due to an increased alveolar number. Our study was conducted in healthy subjects. In the future, it may be of value to investigate the effects of the swimming in people who have airway problems or the other health problems like obesity and also in athletes.